Study Of Coastline Characteristics In Banten Shipping Polytechnic - Rahmat Santoso; Soleh Uddin; Wiratno Wiratno; Mestiria Harbani Sitepu; Mulkan Nuzapril; Rama Agus Mulyadi (Berkala Perikanan Terubuk, 2023)
The character of the coastline is one of the important things to know, this is related to beaches where processes occur due to the influence of coastal conditions in achieving balance with the impacts that occur from natural factors and human activities. Geographically, the beach in the Banten shipping polytechnic area faces the open sea. Abrasion and accreation are very likely to occur on the coastline in the Banten Polytechnic area, soil texture and sedimentation have a big influence on changes in the coastline. This research aims to determine the characteristics of the coastline in the Banten Polytechnic area. The research method uses a descriptive method by tracking along the coastline and taking sediment samples using the methodpurposive sampling. Sampling was carried out in August 2023 with 3 observation stations and each station consisted of 4 observation points. Sample analysis uses the Granulometry method. The results of research on the character of the coastline in the Banten Shipping Polytechnic area show that there are thick piles of rubbish consisting of vegetation and the coastline is experiencing abrasion. The type of coastline sediment in the Banten Polytechnic area has an intermediate sand fraction (4.8%-80.8%) located at soil points A2 and C1, intermediate clay (2.4%-64%) located at soil points B4 and C3, and intermediate dust (15.2%-80.8%) is located at Soil points C1, C2, C3 and A2 with an average texture class having a clay fraction.